Time Extended / 1964 _ 1978. Works and Documents from the Herbert Foundation. - Hanssens, Laura; Herbert, Anton; Morris, Lynda; Richard, Sophie; Ungar, Philippe; Ismail, Samantha; Hanssens, Laura (Gent : Herbert Foundation., 2016)
LeWitt, Sol ; Judd, Donald ; Roth, Dieter ; Barry, Robert ; Richter, gerard ; Siegelaub, Seth ; gevaert, Yves ; Darboven, Hanna;Morris, Lynda ; Moseley, Catherine, Merz, Mario ; Stanley Brouwn
Time extended / 1964 - 1978. Works and Documents from the Herbert Foundation, Herbert Foundation, gent, 16 september 2016
boek